Occupation Of Central Asia By The Soviet Government (Progress Annals: Journal of Progressive Research, 2024)
The occupation of Central Asia by the Soviet government was a significant event in the region's history, marked by a complex and often tumultuous period of Soviet dominance that spanned several decades. From the early 20th century to the dissolution of the Soviet Union in 1991, Central Asia, comprising present-day Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, was subject to Soviet rule, which had far-reaching consequences for the region's politics, economy, culture, and people